Clinical Characterization Pattern of Uterine Fibroids Patients attending to National Ayurveda Teaching Hospital, Sri Lanka - Karunagoda, K.P.K.R.; Perera, P.K.; Senanayake, H. (Institute of Indigenous Medicine, University of Colombo, 2021)
Uterine fibroids (UF) are the most common neoplasm affecting women in reproductive age. Although many studies on the epidemiological factors of UF have been published, such studies are limited on UF cases attended to by the Sri Lankan Ayurveda system. The objective of this study was the clinical characterization of UF patients who visited the Ayurveda gynecology unit in National Ayurveda Teaching Hospital, Borella in the year 2018-2019. This epidemiological, single center study data were collected in two sequential visits. In the baseline visit, the patient was informed of the study and got informed consent and in the next visit completed the data collection, which included epidemiological data, ultrasound UF characteristics and current symptoms. The symptom intensity was assessed by pictorial bleeding assessment score scale (PBAC), UF symptoms and quality of life scale (UFS-QOL) and verbal rating scale (VRS) of pain. Demographic data of UF cases (n=110) was analyzed, maximum in late reproductive life (mean 38.43), nulliparous (57.8%) with 87.5% married and 12.5% unmarried cases. Most prominent associated risk factors identified by the study were nulliparity, high BMI and positive family history. Majority of the fibroid, were diagnosed ≤ 2 years (60%) with no history of myomectomy (66.4%), multiple (64%), intramural type (52.7%), located at uterine corpus (50.9%), UF volume ranged from 03cm3 to 967 cm3 with 26.5 cm3 median. Mean menstruation score reported 55.37 (SD 0.81) by PBAC. Dysmenorrhea, Dyspareunea and Pelvic pain reported as pain symptoms. The heaviness of the abdomen, constipation, urinary problems were the pressure symptoms seen in the study population. Subfertility was 47.1% cases while 12.7% of cases experienced miscarriages. Moderate symptom severity 32.13 (SD ± 15.54) was observed by UFS-QOL. Fertility seems to be the most prominent concern of this study population. Overall moderate symptom intensity was noted, which could be a specific feature of Ayurveda treatment seeking UF population as they attract non-interventional treatment methods.
Keywords: Ayurveda; Uterine fibroids; Clinical characteristics